Analysis for Development of Mocaf-Based Functional Food Industry in Indonesia - Budi Triyono; Setiowiji Handoyo; Nur Laili (Publisher of Widyagama University of Malang (UWG Press), 2019)
Indonesia is a country having abundant natural resources, including nutritious plants as a source of food and medicine. Along with the increasing public awareness of the importance of healthy living, there is a great shift in the demand of food. At present, people do not only want foods that have good nutritional composition as well as attractive appearance and taste, but also the ones that have certain physiological functions for the body. The foods that have such functions are known as functional foods. One ingredient that has the potential to be developed into functional food is mocaf flour. It is made from cassava which is made from the fermentation principle by modifying the cassava cells. This study aims to reveal the conditions for the development of the functional food industry made from mocaf flour in Indonesia using the value chain approach. This study was a qualitative research by using multiple case studies along the value chain. The data were collected from review of secondary data, in-depth interviews, and observations in each case study. The case study locus was the center of the mocaf-based food industry in West Java. The results showed that (i) the mocaf-based functional food industry in Indonesia was not developed; (ii) the development of mocaf-based industries was constrained by the high cost of cassava raw materials; (iii) the productivity of cassava plants was still low; (iv) the role of R & D institutions was very much needed; and (v) government intervention is needed.JEL Classification: L88, O00, Q18